Pengaruh Pemanfaatan Teknologi Informasi Akuntansi dan Pelatihan Akuntansi terhadap Kinerja Keuangan UMKM dengan Disiplin Pencatatan sebagai Variabel Mediasi : Studi Kasus UMKM di Pasar Induk Lau Cih Medan - Satria Abimayu; Lusi Elviani Rangkuti; Heny Triastuti Kurnia Ningsih (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
Small and medium-sized enterprises (SMEs) are the backbone of Indonesia’s economy, providing employment for many people, promoting equitable development, and enhancing the nation’s economic resilience. Sound financial management is essential for businesses to survive. One way businesses can achieve this is by accurately tracking their cash inflows and outflows so they can predict what steps to take to sustain their operations. A lack of knowledge regarding accounting records and the preparation of financial reports that are good, simple, and easy to understand yet compliant with applicable financial standards is a problem frequently faced by businesses. This study was conducted at the Lau Cih Central Market in Medan, with a sample of 100 respondents selected using the Slovin technique. The data analysis technique used was path analysis, comprising model fit tests, the coefficient of determination, hypothesis testing, and the Sobel test. The results of Sub-structure I analysis indicate that the utilization of accounting information technology influences recording discipline, whereas accounting training does not influence recording discipline. Testing of substructure II showed that the use of accounting information technology and recording discipline influence financial performance, whereas accounting training does not influence financial performance. The results of the Sobel test indicate that record-keeping discipline mediates the effect of the use of accounting information technology on financial performance, whereas record-keeping discipline does not mediate the effect of accounting training on financial performance.